Antimicrobial photodynamic therapy mediated by methylene blue and potassium iodide to treat urinary tract infection in a female rat model - Ying-Ying Huang (Nature Portfolio, 2018)
Abstract Drug-resistant urinary tract infections (UTIs) are difficult and sometimes impossible to treat. Many UTIs are caused by uropathogenic Escherichia coli (UPEC). We developed an intact rat model of UTI, by catheterizing female rats and introducing a bioluminescent UPEC strain into the female rat bladder which lasted for up to six days. We recently showed that antimicrobial photodynamic inactivation (aPDI) of a bacterial infection mediated by the well-known phenothiazinium salt, methylene blue (MB) could be strongly potentiated by addition of the non-toxic salt potassium iodide (KI). In the intact rat model we introduced MB into the bladder by catheter, followed by KI solution and delivered intravesicular illumination with a diffusing fiber connected to a 1 W 660 nm laser. Bioluminescent imaging of the bacterial burden was carried out during the procedure and for 6 days afterwards. Light-dose dependent loss of bioluminescence was observed with the combination of MB followed by KI, but recurrence of infection was seen the next day in some cases. aPDT with MB + KI gave a significantly shorter duration of infection compared to untreated controls. aPDT with MB alone was the least effective. No signs of aPDT damage to the bladder lining were detected. This procedure to treat urinary tract infections without antibiotics by using already approved pharmaceutical substances (MB and KI) may have clinical applicability, either initially as a stand-alone therapy, or as an adjunct to antibiotic therapy by a rapid and substantial reduction of the bacterial burden.